Follow-up of the retinal nerve fiber layer thickness of diabetic patients type 2, as a predisposing factor for glaucoma compared to normal subjects - Takis A (Dove Medical Press, 2017)
Alexandros Takis,1 Dimitrios Alonistiotis,1 Nikolaos Ioannou,1 Evgenia Kontou,1 Maria Mitsopoulou,1 Dimitrios Papaconstantinou2 1Second Department of Ophthalmology, University of Athens, “Attikon” Hospital, Athens, 2First Department of Ophthalmology, University of Athens, General Hospital of Athens “G Genimatas”, Athens, Greece Purpose: To evaluate and follow-up the retinal nerve fiber layer (RNFL) thickness in patients with diabetes mellitus type 2 compared to a group of healthy individuals with similar demographic characteristics.Patients and methods: This is a prospective, noninvasive, observational case series study. For the purposes of the study, 27 eyes of diabetic patients without diabetic retinopathy, 24 eyes of patients with mild retinopathy, and 25 normal age-matched subjects (control group [CG]) were examined. All participants underwent complete ophthalmological examination and imaging with GDx variable corneal compensation scanning laser polarimetry. Follow-up was 2 years for all three groups.Results: The mean inferior average was statistically significantly lower in both diabetic groups compared to CG at baseline examination and during follow-up. The nerve fiber indicator (NFI) was higher in both diabetic groups compared to CG, both at baseline examination and during follow-up. The NFI was 21.7±11.9 and 22.0±11.8 for the diabetic group without retinopathy, 20.8±9.6 and 21.9±9.8 for the group with mild retinopathy, and 15.3±5.4 and 15.9±5.5 for the normal subjects, at baseline and 24 months, respectively. There was no statistically significant reduction of the RNFL thickness in all three groups compared to baseline examination.Conclusion: This is the first long-term study documenting the RNFL thickness in diabetic patients in comparison with normal controls. Although the lower RNFL was found thinner in diabetics, the 2-year follow-up showed no significant reduction of RNFL thickness in all groups, indicating that RNFL damage may occur early in diabetic patients. Keywords: RNFL, GDx, diabetic retinopathy, glaucoma